2019
DOI: 10.3892/or.2019.7148
|View full text |Cite
|
Sign up to set email alerts
|

The targeting of non‑coding RNAs by curcumin: Facts and hopes for cancer therapy (Review)

Abstract: Curcumin [(1E,6E)-1,7-bis(4-hydroxy-3-methoxyphenyl) hepta-1,6-diene-3,5-dione] is a natural polyphenol that is derived from the turmeric plant ( curcuma longa L.). Curcumin is widely used in food coloring, preservatives, and condiments. Curcumin possesses anti-tumor, anti-oxidative and anti-inflammatory efficacy, as well as other pharmacological effects. Emerging evidence indicates that curcumin alters microRNAs (miRNAs) and long non-coding RNAs (lncRNAs) in various types of cancers. Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 120 publications
(125 reference statements)
0
35
0
Order By: Relevance
“…Plants have long been considered a rich source of bioactive natural products, some of which exhibit potent activity as potential anticancer agents (3)(4)(5)(6)(7). Costunolide is a sesquiterpene lactone (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Plants have long been considered a rich source of bioactive natural products, some of which exhibit potent activity as potential anticancer agents (3)(4)(5)(6)(7). Costunolide is a sesquiterpene lactone (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The use of natural compounds and medicinal based plants for health promotion and adjuvant therapy is becoming increasingly popular worldwide (Li et al, 2019;Liu et al, 2019c). Zicao has been used as an effective treatment for a variety of inflammatory and infectious diseases for a long history.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in CRC, curcumin reversed oxaliplatin resistance via regulating the process of epithelial-mesenchymal transition [33]. What's more, Liu et al [34] reported that the regulatory effect of curcumin on LncRNAs in CRC. Therefore, we speculated that curcumin may reserve chemotherapy drug resistance in CRC via modulating LncRNAs.…”
Section: Discussionmentioning
confidence: 99%